Sodium montmorillonite/ureasil-poly(oxyethylene) nanocomposite as potential adsorbent of cationic dye - Bermudez, Yanisleidys Hernandez [UNESP]; Truffault, Laurianne [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V., 2018)
A sodium montmorillonite/ureasil-poly(oxyethylene) clay-polymer nanocomposite was prepared using the solgel reaction of a U-PEO hybrid precursor/clay mineral suspension, with the aim of developing a sorbent for the removal of cationic dyes from aqueous media. The structural characteristics of the nanocomposite were studied by FTIR, XRD, UV Vis spectroscopy, and SAXS. The XRD results revealed intercalation of the U-PEO in the silicate interlayer spaces. FTIR spectra indicated the existence of strong interactions between methylene blue (MB) dye and the clay mineral silicate layers. Time-resolved SAXS measurements during MB adsorption showed a decrease of the montmorillonite (Mt) peak area and an increase of the half-height width of the peak, indicating that water uptake during dye adsorption caused a reduction of the Mt. crystallite size. UV Vis adsorption experiments showed that the kinetics of MB adsorption followed a pseudo-first order process and that the steady state equilibrium adsorption capacity followed the Langmuir model. The results showed that the nanocomposite is potentially applicable as an adsorbent of dyes present in contaminated waters.
Keywords: Montmorillonite; Nanocomposite; Dye; Adsorption; Water decontamination